2009
DOI: 10.1200/jco.2009.27.15_suppl.8582
|View full text |Cite
|
Sign up to set email alerts
|

An open-label, multicenter, phase II study of AT-101 in combination with rituximab (R) in patients with untreated, grade 1-2, follicular non-Hodgkin's lymphoma (FL)

Abstract: 8582 Background: Bcl-2 family proteins are overexpressed in the majority of patients with FL and contribute to resistance to therapy. AT-101 is a pan-Bcl-2 inhibitor (Bcl-2, Bcl-XL, Bcl-W, and Mcl-1) and potent inducer of proapoptotic proteins. It is active as a single agent and in combination with R in NHL tumor models. Methods: Patients with untreated FL who did not require immediate chemotherapy were eligible. Treatment consisted of an induction cycle of AT-101 (30mg po daily × 21) and R (375 mg/m2 weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The same group published findings from investigations conducted using AT-101 (a BH3 mimetic) [23]. In vitro, AT-101 exhibited concentration-and time-dependent cytotoxicity against lymphoma and multiple myeloma cell lines, and enhanced the activity of cytotoxic agents.…”
Section: Dosing Schedule Considerations For Clinical Trial Designmentioning
confidence: 96%
See 1 more Smart Citation
“…The same group published findings from investigations conducted using AT-101 (a BH3 mimetic) [23]. In vitro, AT-101 exhibited concentration-and time-dependent cytotoxicity against lymphoma and multiple myeloma cell lines, and enhanced the activity of cytotoxic agents.…”
Section: Dosing Schedule Considerations For Clinical Trial Designmentioning
confidence: 96%
“…In preclinical models, AT-101 has been shown to synergize with conventional chemotherapy in models of DLBCL and mantle cell lymphoma (MCL) [22]. One phase II study has reported results in 23 patients with untreated FL, and although treatment was well tolerated, the combination of AT-101 and rituximab achieved a response rate following induction of 26% (95% CI = 10.2-48.4), with 4% complete response (CR); the best ORR was 70% (95% CI = 47.1-86.8), with a 35% CR [23]. A randomized trial will be required to definitively determine the level of activity of AT-101 and rituximab in patients with lymphoma.…”
Section: Bcl-2 As a Therapeutic Targetmentioning
confidence: 99%